Micropropagation techniques as tools for studying plant growth, tuberization and sprouting of potatoes - Alsadon, Abdulla A., author; Knutson, Kenneth W., advisor; Hanan, Joe J., committee member; Fenwick, Jack R., committee member; Wallner, Stephen J., committee member; Moore, Frank D., III, committee member (Colorado State University. Libraries, 1988)
Several investigations were undertaken to determine if micropropagated potato cultivars of different maturity classes performed under field conditions in a manner similar to that reported for seed tuber propagated plants of the same cultivars. Plant growth analysis was carried out with special emphasis using Richards' function for evaluating growth attributes such as plant height, leaf area, and derived growth quantities such as RGR. Early, medium, and late maturing potato cultivars were grown under field, greenhouse and vitro conditions to measure tuber yields. Two sprouting indices (sprouting rate index, and sprouting ratio index) were developed and used to quantify the sprouting characteristics of field, greenhouse, and in vitro produced tubers. Storage temperatures were 5, 10, and 20° C. The combined field data of 1986 and 1987 indicated that plant growth, development and tuber yield were in general agreement to that of seed tuber propagated plants. The derived growth quantities (i.e. RSER, RLAER, RTGR, and RUGR) provided a useful way of comparing cultivar response and explained how the overall growth and development can be understood. Significant correlations were reported between selected yield characteristics of field grown, greenhouse grown and in vitro produced tubers. Both Kennebec and Spunta had the highest yield under field, greenhouse, and in vitro conditions. Russet Burbank and Norland had the lowest yield while Desiree and Norgold Russet had an intermediate response. Both sprouting indices incorporate the influence of factors such as cultivar, temperature and tuber size. Both indices also indicate that earliest sprouting occurred in Norland followed by Desiree and Russet Burbank. Field grown, and greenhouse grown tubers exhibited earlier sprouting than] in vitro produced tubers. Overall, these investigations illustrate the potential value of micropropagation methods in predicting yielding ability and sprouting characteristics of potato cultivars.
Covers not scanned.
Keywords: Potatoes; Plant micropropagation